(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
The article discusses one of the most popular animals in folk literature – the fox, in such different Eastern folklore as Chinese and Persian. It compares the role of the fox in the fables and animal tales, identifies differences and similarities of using this character in the fairy tales of two countries. As literature is one of the tools which always used to reflect reality, the study of such ancient literary genre as fairy tale, allows lifting the veil and showing the realities of two cultures. Thus, a comparative analysis of the article can be used to further study the reflections and worldviews of the two poles of one East.